Understanding Autonomous Cooperation and Control in Logistics The Impact of Autonomy on Management, Information, Communication and Material Flow - Hülsmann, Michael; Windt, Katja (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Autonomous co-operation addresses the control problem of logistic processes characterized by dynamical changing parameters and complex system behaviour. During control procedures erratic, non-predictable changes of parameters can occur. Therefore, future planning and control has to face severe and vital uncertainties. Conventional hierarchical systems are amplifying these difficulties because of the additional time delay of information transfer and additional calculation time. On the other hand, autonomous co-operation enables logistic objects (e.g. a single container) in decentralized structures to collect and evaluate information simultaneously to any event of change, so that they can render and execute decisions on their own. Therefore, this book aims to give a profound understanding of autonomous co-operation and to examine its potentials to increase the robustness and positive emergence of logistic processes substantially.